The impact of asymptomatic intracranial atherosclerotic stenosis on the clinical outcomes of patients with single subcortical infarction - Yang, Yi; He, Yue; Xu, Yuhao; Han, Wei; Shao, Yuanwei; Zhao, Tian; Yu, Ming (Frontiers in Medicine, 2023)
The presence of parental arterial disease (PAD) is correlated with the outcomes of patients with single subcortical infarction (SSI). Due to the relatively low incidence of PAD, the predictors of the outcomes seem to be limited for SSI patients without PAD. This study aims to investigate the association between the asymptomatic intracranial atherosclerotic stenosis (aIAS) and outcomes of patients with SSI and of the subgroup without PAD. Methods: Patients with SSI were consecutively enrolled. aIAS referred to a stenosis of ≥ 50% in intracranial arteries irrelevant to SSI by using magnetic resonance angiograph. A poor outcome referred to a modified Ranking Scale > 2 points at discharge. Results: 298 participants were enrolled. The presence of aIAS could predict a poor outcome of all SSI patients [adjusted relative risk (aRR) = 2.14, 95% confidence interval (CI) = 1.17-3.93, p = 0.014] and of the subgroup without PAD (aRR = 3.12, 95% CI = 1.47-6.62, p = 0.003), but could not in the subgroup with PAD. Compared with participants with neither aIAS nor PAD, the risk of a poor outcome increased approximately 2-fold in those with aIAS only (aRR = 2.95, 95% CI = 1.55-5.60, p = 0.001) and in those with concomitant aIAS and PAD (aRR = 3.10, 95% CI = 1.62-5.95, p = 0.001). Conclusion: The presence of aIAS is a predictor of a poor outcome in SSI patients, especially in those without PAD.